Haemolytic uraemic syndrome / thrombocytopaenic thrombotic purpura - Pessegueiro, Pedro (2004)
Haemolytic uraemic syndrome and thrombocytopenic thrombotic purpura are characterized by the presence of haemolytic microangiopathic anaemia and thrombocytopenia. The endothelial dysfunction and the release of von Willebrand factor high molecular weight multimers are implicated in the sequence of events that lead to microvascular thrombosis. The high plasma level of lactic dehydrogenase is the most sensitive index for the ongoing microangiopathic haemolysis.In haemolytic uraemic syndrome the microthrombi are confined to the kidney, being the acute renal failure the dominant clinical feature. Thrombocytopenic thrombotic purpura affects mainly the brain, with intermittent thrombi formation and presenting fl uctuating neurological symptoms.The authors review the major characteristics, clinical features, prognosis and treatment of the primary and secondary haemolytic uraemic syndrome / thrombocytopenic thrombotic purpura forms, as well as the acute, chronic, recurrent and plasmapheresis resistant presentations.